Neodymium isotopic composition in foraminifera and authigenic phases of the South China Sea sediments: Implications for the hydrology of the North Pacific Ocean over the past 25 kyr. (11th November 2015) - Wu, Qiong; Colin, Christophe; Liu, Zhifei; Thil, François; Dubois‐Dauphin, Quentin; Frank, Norbert; Tachikawa, Kazuyo; Bordier, Louise; Douville, Eric
Abstract: εNd and normalized Rare Earth Elements (REE) patterns of benthic and planktonic foraminifera and Fe‐Mn coatings precipitated on sediments have been investigated for the South China Sea (SCS) to (1) assess the reliability of the extraction of past seawater εNd in the SCS and to (2) reconstruct past hydrological changes during the last 25 kyr. Reductively cleaned mono‐specific planktonic foraminifera ( Globigerinoides ruber ) and mixed benthic foraminifera in core‐top sediments from 1500 to 2400 m display similar εNd values to those of the modern Pacific Deep Water (PDW) (εNd of −3.9 to −4.4). Furthermore, the εNd of the reductive cleaning solutions shows similar εNd values to ones obtained on cleaned foraminifera. Combined with PAAS‐normalized REE patterns, these results confirm that the oxidative and reductive cleaning procedure applied to foraminifera does not totally remove all of the Fe‐Mn coatings and that εNd values yielded by cleaned planktonic foraminifera retain the εNd imprint of the bottom and/or pore water. εNd values obtained from a leaching procedure carried out on the bulk non‐decarbonated sediments are comparable to the εNd values of the modern PDW, whereas a similar leaching procedure applied to decarbonated sediments reveals a bias due to contamination with Nd deriving from lithogenic particles. In core MD05‐2904, seawater εNd, reconstructed from planktonic foraminifera, indicates that the last glacial period is characterized by lower εNd (−5.2 ± 0.2 to −6.4 ± 0.3) than the late Holocene (−4.1 ± 0.2). Assuming that Nd input from river does not change strongly the εNd of the PDW of the northern SCS, these εNd variations suggest a higher relative proportions of southern‐sourced water in the deep water of the western subtropical Pacific Ocean during the last glacial period. Key Points: εNd of foraminifera investigated for the first time in the South China Sea Improvement of the extraction of seawater Nd isotopes from marine sediments Past hydrological changes in the subtropical Pacific for the last 25 kyr